Homo-oligomerization of the Activating Natural Killer Cell Receptor NKp30 Ectodomain Increases Its Binding Affinity for Cellular Ligands - Herrmann, Julia (American Society for Biochemistry and Molecular Biology, 2014)
The natural cytotoxicity receptors, comprised of three type I membrane proteins NKp30, NKp44, and NKp46, are a unique set of activating proteins expressed mainly on the surface of natural killer (NK) cells. Among these, NKp30 is a major receptor targeting virus-infected cells, malignantly transformed cells, and immature dendritic cells. To date, only few cellular ligands of NKp30 have been discovered, and the molecular details of ligand recognition by NKp30 are poorly understood. Within the current study, we found that the ectodomain of NKp30 forms functional homo-oligomers that mediate high affinity binding to its corresponding cellular ligand B7-H6. Notably, this homo-oligomerization is strongly promoted by the stalk domain of NKp30. Based on these data, we suggest that homo-oligomerization of NKp30 in the plasma membrane of NK cells, which might be favored by IL-2-dependent up-regulation of NKp30 expression, provides a way to improve recognition and lysis of target cells by NK cells.